Comparative Analysis of Camellia and AES Across File Sizes and Types - Teja Endra Eng Tju; Fauzi Alfadhillah (UIN Sunan Kalijaga Yogyakarta, 2026)
Data security is a critical aspect of modern information systems that requires processing cryptographic efficiency and resilience. This study compares two widely used symmetric encryption algorithms, named Camellia and AES, based on their performance and resistance to standard attack methods. An experimental approach was applied using 72 files across eight commonly used formats (*.mp3, *.jpg, *.png, *.pdf, *.docx, *.xls, *.pptx, and .txt) in three predefined sizes: 100 KB, 1 MB, and 10 MB. Each file underwent encryption and decryption in a controlled environment, with metrics such as processing time, CPU usage, and RAM consumption recorded. Simulated Dictionary, Birthday, and Brute-Force attacks were conducted to assess algorithm robustness. Results show that AES performs faster, especially on large files, but with higher memory usage. Camellia demonstrated more consistent RAM usage and stronger resistance, successfully withstanding all attacks except one brute-force case on a small plaintext file. AES suffered multiple breaches on structured files of smaller sizes. The findings suggest that algorithm selection should consider workload characteristics and system constraints. The main contribution of this research lies in its comprehensive dataset and empirical comparison, providing practical insights to support encryption algorithm choices in real-world applications.